Evaluating Strategies to Improve Water Availability and Lateral Root Growth of Plants Grown in the Rice-Growing Lowlands of the Lower Mekong Basin - Ballester, Carlos; Hornbuckle, John; Inthavong, Thavone; Lim, Vanndy; McCormick, Jeffrey; Molesworth, Anika; Oeurng, Chantha; Quayle, Wendy; Seng, Vang; Sengxua, Pheng; Sihathep, Vorachith; Touch, Veasna; et al. (Agronomy (Basel), 2021)
Overcoming constraints that poorly structured lowland rice-growing soils of the Lower Mekong River Basin present for growing non-rice crops during the dry season would have a significant positive impact on the livelihood of smallholder farmers. This study investigated whether the use of soil organic amendments, bed architecture (conventional, flat and narrow) and water application methods (sprinkler, furrow and over-bed irrigation) could improve plant water availability in typical rice-growing soils of Cambodia and Laos by either improving the movement of water into beds or the growth of the root system. Five experiments were conducted over two dry seasons on peanut and maize grown in a bed/furrow system. Organic amendments assessed were rice straw, cow/goat manure, biochar, manure plus rice straw and biochar plus manure. Results showed that compared with conventional bed/furrow design, narrowing beds increased soil moisture availability for peanut, whilst higher grain yield and water productivity were achieved with sprinkler irrigation than furrow irrigation. Placing a layer of sub-surface straw within beds did not consistently enhance soil moisture or improve root development. The study showed that maize grown on soil amended with biochar plus cow manure under a furrow irrigation system and on rice straw under sprinkler irrigation produced yields above the average yield that models have simulated for maize grown on these soils. These findings present opportunities to enhance maize production on lowland soils across Cambodia and Laos. The contrary was observed for peanut production, which indicates that factors other than water might be detrimentally affecting crop yields.